SOLUTION OF GENERAL AND PREVENTION OF ECOLOGICAL PROBLEMS OF STARA PLANINA MOUNTAIN AS POTENTIAL OBSTACLES TO THE DEVEOPMENT OF RURAL TOURISM - Maksimović, Mladjan; Janovac, Tatjana; Karabašević, Darjan; Brzaković, Miodrag (Economics of Agriculture, 2018)
The development of rural tourism positively affects the economic development of rural communities, but the very pace of its development often results in negative effects on the environment. Uncontrolled rural tourism development, without an adequate planning system, can greatly endanger the entire ecosystem of a destination. The aim of this paper is to determine how much the development of rural tourism on Stara Planina Mountain depends on the solution of general and prevention of ecological problems. A method that allows the cause-effect relationships between these phenomena is a linear regression analysis. This analysis best describes the quantitative dependence between the variations of the observed phenomena in real conditions. It represents the means that enable us to evaluate and predict the values of the dependent variable for the desired values of the explanatory variable. In other words, the main issue is rural tourism on Stara Planina Mountain, which depends on the solution of general and prevention of environmental problems.